Metal-Templated Hydrogen Bond Donors as "Organocatalysts" for Carbon-Carbon Bond Forming Reactions: Syntheses, Structures, and Reactivities of 2-Guanidinobenzimidazole Cyclopentadienyl Ruthenium Complexes - Scherer, Alexander; Mukherjee, Tathagata; Hampel, Frank; Gladysz, John (Organometallics, 2014)
The reaction of 2-guanidinobenzimidazole (GBI) and (eta(5)-C5H5)Ru(PPh3)(2)(Cl) in refluxing toluene gives the chelate [(eta(5)-C5H5)Ru(PPh3)(GBI)]Cl-+(-)(1(+)Cl(-); 96%). Subsequent anion metatheses yield the BF4, PF6, and BA(4) (B(3,5-C6H3(CF3)(2))(4)(-)) salts (7785%). Reactions with CO give the carbonyl complexes [(eta(5)-C5H5)Ru(CO)(GBI)]X+ (2+X; X = Cl, BF4, PF6, BA(4); 8792%). The last three salts can also be obtained by anion metatheses of 2+Cl (7787%), as can one with the chiral enantiopure anion P(o-C(6)Cl4O2)3 ((?)-TRISPHAT; 81%). The reaction of [(eta(5)-C5H5)Ru(CO)(NCCH3)(2)]+PF6 and GBI also gives 2+PF6 (81%). The pentamethylcyclopentadienyl analogues [(eta(5)-C5Me5)Ru(CO)(GBI)]X+ (3+X; X = Cl, BF4, PF6, BA4; 6184%) are prepared from (eta(5)-C5Me5)Ru(PPh3)(2)(Cl), GBI, and CO followed (for the last three) by anion metatheses. An indenyl complex [(eta(5)-C9H7)Ru(PPh3)(GBI)]Cl+ (96%) is prepared from (eta(5)-C9H7)Ru(PPh3)(2)(Cl) and GBI. All complexes are characterized by NMR (H-1, C-13, P-31, F-19, B-11), with 2D spectra aiding assignments. Crystal structures of 1+PF6.CH(2)Cl2 and 1(+)BA4 CH2Cl2 are determined; the anion is hydrogen bonded to the cation in the former. Complexes 13(+)X are evaluated as catalysts (10 mol %, RT) for condensations of indoles and trans-beta-nitrostyrene. The chloride salts are ineffective (05% yields, 4860 h), but the BArf salts exhibit excellent reactivities (9746% yields, 148 h), with the BF4 and PF6 salts intermediate. Evidence for hydrogen bonding of the nitro group to the GBI ligand is presented. GBI shows no catalytic activity; a BArf salt of methylated GBI is active, but much less so than 23+BAr